How electronic devices affect the sleep of young people: summary of current knowledge - Sysło, Oliwia; Jung, Maximilian; Jung, Magdalena; Jaworski, Aleksander; Słowińska, Barbara; Jasiński, Dawid; Jung, Samuel; Woźniak, Kinga; Jędral, Krystian; Czyż, Sandra (Journal of Education, Health and Sport, 2024)
Introduction and purpose: The impact of electronic devices on our daily lives is becoming increasingly significant. The contemporary generation of young people is growing up in a world where smartphones, tablets, computers, and other electronic devices are widely available and utilized. Scientists are contemplating the challenges posed by excessive exploitation of electronics on the health of young individuals. The aim of the article is to present the harmful effects of using electronic devices before sleep in young people, considering medical aspects such as sleep disorders and their influence on overall psychophysical health. Summary: Electronic devices negatively affect the sleep of young people by reducing sleep time and delaying the sleep onset phase. The main problem is the use of electronic devices without time limits. In the era of technology, it is significantly important to raise awareness among young people about the importance of sleep hygiene and how blue light emitted by electronic devices affects its quality.